2015
DOI: 10.1002/ajim.22424
|View full text |Cite
|
Sign up to set email alerts
|

The Inclusion of Women in Studies of Occupational Cancer: A Review of the Epidemiologic Literature From 1991–2009

Abstract: Despite advances in the inclusion of women in studies of occupational cancer, disparities remain in the number of studies of occupational cancer and depth of analysis in studies that included women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 13 publications
4
22
0
Order By: Relevance
“…Our results suggest that the inclusion of women in studies regarding occupational lung cancer remains minimal, as shown by the very few women‐only studies and the largely disproportionate men‐to‐women ratio among mixed studies. This observation is consistent with Niedhammer et al and Hohenadel et al studies, in which they found for the broader categories of cancers and respiratory cancers respectively, men to be included in 90.8% and 95.2% of studies (compared to a combined 97.1% of men's inclusion in our study), against 46.1% and 43.2% for women (44.4% in our study) . Two main hypotheses may be formulated while interpreting this men‐centered distribution.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Our results suggest that the inclusion of women in studies regarding occupational lung cancer remains minimal, as shown by the very few women‐only studies and the largely disproportionate men‐to‐women ratio among mixed studies. This observation is consistent with Niedhammer et al and Hohenadel et al studies, in which they found for the broader categories of cancers and respiratory cancers respectively, men to be included in 90.8% and 95.2% of studies (compared to a combined 97.1% of men's inclusion in our study), against 46.1% and 43.2% for women (44.4% in our study) . Two main hypotheses may be formulated while interpreting this men‐centered distribution.…”
Section: Discussionsupporting
confidence: 93%
“…The type of exposure variable is also of importance, as studies presenting continuous estimates for exposure are likely to produce more precise risk estimates, and further initiate dose‐response analysis. Our sample suggest that mixed studies with higher men‐to‐women ratios were more likely to use continuous estimates; a result in accordance with Hohenadel et al who reported more dose‐response evaluation among studies including men, compared to studies including women‐only.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations